Ayurvedic management of childhood stable plaque psoriasis: A case report (Indian Journal of Case Reports, 2020)
Psoriasis causes disfigurement of skin and can cause significant psychological effects in the patient. The onset of psoriasis in childhood is common. Systemic treatments and phototherapy have been of limited use in children and are found to have gonadal toxicity. In the present case report, a case of childhood psoriasis was treated with a course of Virechana, a form of purification procedure and internal administration of Guggulutiktaka Ghrita and Mahatiktaka Kashaya along with an external application of 777 oil. After 4 months of treatment, a complete remission of the disease was observed with the Psoriasis Area and Severity Index score getting reduced from 32.8 before treatment to 0 after treatment. This suggests Ayurvedic classical treatment can modify the disease process in psoriasis.